Model Spasial Pendugaan Biomassa Di Atas Permukaan Tanah Di Hutan Nagari Padang Limau Sundai Kabupaten Solok Selatan Provinsi Sumatera Barat - Achmad, Eva; Nursanti, Nursanti; Manalu, Joy Halomoan Boang (Fakultas Kehutanan Universitas Jambi, 2018)
Biomass estimation model can be derived from satellite imageries and field measurements. This study built the estimation model using Landsat 8 image. This study was conducted in Hutan Nagari Padang Limau Sundai Sangir Jujuan, South Solok District, West Sumatera Province. This study aimed to build biomass estimation model and to study distribution of biomass over forest area using digital number of bands 4, 5, 6 and Normalized-Difference of Vegetation Indeks (NDVI). Field biomass was estimated using allometric Ketterings (2001). The biomass estimation model were developed using regression analysis by relating field biomass value and digital number of Landsat 8 Imagery. Selection of the best model based on the highest R2adj value, the lowest standard deviation value, the lowest bias value, and the lowest Root Mean Square Error (RMSE). Based on the result of model analysis to estimate biomass, obtained the best biomass estimate model, that is exponential model, Y = e (-27,40707 + 0,00461 X4 -0,00011 X5 - 0,00197 X6 + 50,79023 NDVI). The model selected based on the rating result had R2adj 78,8 %, standart deviation 0,227, bias 1,21 and RMSE 14,89.